Pengelolaan Sampah Berbasis Masyarakat sebagai Upaya Mewujudkan Kota Layak Huni di Kelurahan Bulusan Tembalang Semarang - Santy Paulla Dewi; Nurini Nurini; Diah Intan Kusumo Dewi; Grandy Lorenessa Wungo (Warta LPM, 2022)
The increasing of population number influences waste generation so that it requires proper management to prevent the environmental problems. Waste management will determine the level of environment quality as well as the amenities. This is in accordance with the concept of a livable city, particularly related to the provision of urban facilities. Hence, it is necessary to have an understanding of the concept of a livable city as a form of the government's commitment to improving the quality of the environment and society. The community service team is from the Laboratory of Urban Design and Development, Department of Urban and Regional Planning, Universitas Diponegoro that consist of four lecturers and two students disseminated the concept of a livable city in Bulusan Village through community-based waste management. This is done as an effort to reduce the volume of waste which requires an active role and community commitment. The purpose of this dissemination is to increase public understanding and ultimately realize the importance of playing a role in its implementation. The method used in this activity were identified potentions and problems on waste management, identified the community’s characteristics and analyzed existing waste management, that further arranged the waste management strategies in term of liveable city. The data collection process is carried out through interviews and field observations. The output of this community service is a community-based waste management strategy within the framework of the livable city concept based on lessons learned from best practices and relevant theories through the involvement of students, boarding house owners, and the community in waste sorting, the role of government in bridging with garbage collectors.